A formação humana como ponto de confluência na Pedagogia de Rousseau - Becker, Patrícia Tarouco Manetti (2012)
The present study, based on a bibliographical methodology, aims to discuss the contributions of Jean-Jacques Rousseau to the educative and formative processes in present days. For this purpose, we defend reflections adduced in the author s thought. First, we make a special distinction to the Genebrian thinker s history of life. Secondly, as from his books investigation, we expose the basis that subsidize human formation concept. With these information, humanizing aspects of formation in man s constitutive trajectory are discussed. The debate about questions related to formative processes in school are also brought. During this investigation development, based on rousseaunian theory, we observe the potentialities offered by Rousseau s educational philosophy in present days. The assertive becomes valid because his work represents a classic theory, which is able to overcome temporality and makes happen discussions in different contexts. Regarding to human formation, rousseaunian thought offers to the educative act a reflection about the necessity of comprehension that formation process involves family participation when it refers to human values, limits, morality in actions, in education through examples, since theses categories, facing what is presented in educational reality make potent (as historical horizon) an absolute fulfillment of human formation. The investigation s focus is to present the contributions of rousseaunian pedagogy to children formation, the one that will result in adults formation.